Pendidikan Agama Islam Anak dalam Keluarga Broken Home : Studi Kasus Desa Minanga Kecamatan Rongkong - Saepul; Nur Mita sari (South Sulawesi Education Development, 2025)
Children's Islamic religious education in the family cannot be separated between education in the family, school, and community. Put simply, education is a human effort to develop children's personalities and internal values. Family and education are two terms that cannot be separated because education is where there is a family. When there are parents who want to educate their children, then at the same time there is also a parent's responsibility towards their children. In addition, the author will discuss Islamic religious education for children in broken home families (a case study in Minanga Village, Rongkong District). The problems in this article will focus on first, how foster parents or foster parents apply to children's religious education in Broken Home families; second, what are the supporting and inhibiting factors for Islamic religious education in Broken Home families in Minanga Village, Rongkong District; third, this article is the result of qualitative descriptive research that the author conducted in Minanga Village. The study conducted by the author showed that Islamic religious education in Broken Home families varied in the application of their religious education. One family was not appropriate in their religious education because they were busy. Five families were not appropriate in their religious education. Applicable in the religious education of their children.